TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP NASABAH DALAM TRANSAKSI GIRO PERBANKAN DI INDONESIA - Haryono . (Jurnal Surya Kencana Dua : Dinamika Masalah Hukum dan Keadilan, 2016)
Bank is a financial institution that plays a strategic role to promote the economy of a country. Indeed, in its development the banking sector plays a very important role in the economy of a country. Therefore, if the banking sector is experiencing a crisis, it will have an impact on the Indonesian economy.Keywords: Protection, customers, banking